2012
DOI: 10.4317/medoral.18041
|View full text |Cite
|
Sign up to set email alerts
|

Oral bisphosphonate-related osteonecrosis of the jaws: Clinical characteristics of a series of 20 cases in Spain

Abstract: Objective: The objective of this study was to define the clinical characteristics of osteonecrosis of the jaws (ONJ) induced by oral bisphosphonates in a series of patients from a circumscribed area in northwest Spain. Study Design:A retrospective multicentre study was undertaken in 3 hospitals in an area with a radius less than 100 km in the Autonomous Community of Galicia (Spain). The medical records were reviewed and an oral examination was performed of patients diagnosed with oral bisphosphonate-related ON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
35
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 33 publications
10
35
0
3
Order By: Relevance
“…Such a fact would indicate that the short time period of BP exposure may not always necessarily constitute a safety threshold relating to the risk of BRONJ in any given patient and, in every case, the tailoring of BP therapy to individual patients would be beneficial. The most frequent observation in our sample of the AAOMS stage 2 BRONJ (60.9%) correlates with the data reported in other studies [5,12,16,31]. It is our opinion that this frequent datum is relevant to explaining the incidence of a tardy BRONJ diagnosis, either due to delay, a misdiagnosis or a low level of awareness by the physician.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Such a fact would indicate that the short time period of BP exposure may not always necessarily constitute a safety threshold relating to the risk of BRONJ in any given patient and, in every case, the tailoring of BP therapy to individual patients would be beneficial. The most frequent observation in our sample of the AAOMS stage 2 BRONJ (60.9%) correlates with the data reported in other studies [5,12,16,31]. It is our opinion that this frequent datum is relevant to explaining the incidence of a tardy BRONJ diagnosis, either due to delay, a misdiagnosis or a low level of awareness by the physician.…”
Section: Discussionsupporting
confidence: 89%
“…Concurring with other authors [11][12][13]32,41], we observed and described 87 cases of BRONJ in patients taking oral BPs; these cases have been described and correlated with other cases [5,12,16,31], mainly occurring in the mandible (73.6%). One limitation of our research was the non-controlled study design which may have led to an overestimation of BRONJ in non cancer-patients.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…[4] On the other hand, prolonged therapy with bisphosphonates, adversely leads to ON of the jaws in some patients. [14] Bisphosphonates associated ON rarely occurs in the long bones, only one case was reported on zoledronic acid therapy. [15] In a study, 20 cases of bisphosphonate-related osteonecrosis were reviewed and 16 alendronate and four ibandronate usage were reported.…”
Section: Discussionmentioning
confidence: 99%